2020
DOI: 10.1186/s13613-020-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ventilator-associated events for the diagnosis of ventilator-associated lower respiratory tract infections

Abstract: Background: The aim of this study was to investigate the concordance between ventilator-associated events (VAE) and ventilator-associated lower respiratory tract infections (VA-LRTI), and their impact on outcome.Methods: This retrospective study was performed in five 10-bed ICUs of a teaching hospital, during a 2-year period. Ventilator-associated lower respiratory tract infections (VA-LRTI), including ventilator-associated tracheobronchitis (VAT) and ventilator-associated pneumonia (VAP) were prospectively di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This result may also be analyzed in regards of the criteria issued by the CDC for the diagnosis of ventilator-associated events, based on the presence of gas exchange worsening [ 10 ]. Even though developed for a purpose of reproducibility, these criteria seem to show a poor agreement with the classical definition of VAP, as outlined by several studies [ 7 , 11 , 12 ]. Our results, showing that severity of hypoxemia exhibited poor accuracy for the diagnosis of VAP tend to support these data.…”
Section: Discussionmentioning
confidence: 96%
“…This result may also be analyzed in regards of the criteria issued by the CDC for the diagnosis of ventilator-associated events, based on the presence of gas exchange worsening [ 10 ]. Even though developed for a purpose of reproducibility, these criteria seem to show a poor agreement with the classical definition of VAP, as outlined by several studies [ 7 , 11 , 12 ]. Our results, showing that severity of hypoxemia exhibited poor accuracy for the diagnosis of VAP tend to support these data.…”
Section: Discussionmentioning
confidence: 96%
“…However, VAE surveillance is insensitive for identifying VAP 30 . A recent study confirmed that there was poor agreement between VAE and VAP 31 . Therefore, the outcomes of patients with VAE may be different from those with VAP.…”
Section: Discussionmentioning
confidence: 96%
“…1 ). These cutoff points for the three groups were chosen as a bacterial density of 10 5 ‒10 6 cfu/mL in ETA is frequently used as the threshold for diagnosing VA-LRTI [ 1 , 11 , 12 ]. ETA samples were taken on admission and then once weekly during ICU stay.…”
Section: Methodsmentioning
confidence: 99%